Musca, Giosué. Il vangelo e la torah. Cristini ed ebrei nella prima crociata. Bari: Dedalo, 1999, 126 pp. - Hubeñak, Florencio (2000)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina